High-adhesion non-traumatic separable gel adhesive and preparation method and application thereof
By copolymerizing the fluorine-containing cationic surfactant with sodium citrate, trifluoroethylacrylate and acrylic acid, a gel adhesive with strong adhesion and non-traumatic separation is prepared, and the bonding in the prior art is solved The problem of harsh damage to soft surfaces and deadhesion conditions of the agent achieves stable adhesion and deadhesion under mild conditions, and is suitable for a variety of applications.
Patent Information
- Application Number
- CN202411202552.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-14
AI Technical Summary
Existing gel adhesives are difficult to meet both strong adhesion and non-traumatic deadhesion, especially on soft surfaces, and the deadhesion conditions of existing reversible adhesive gel-type adhesives are harsh. Limits its application.
Fluorine-containing cationic surfactant, sodium citrate, trifluoroethylacrylate and acrylic acid are used to copolymerize to form a gel adhesive with strong adhesion and good mechanical properties, and non-invasive treatment is achieved through water or ethanol treatment. Sexual separation.
The prepared gel adhesive has strong adhesion, low skin irritation, good mechanical properties and electrical conductivity, and can achieve a stable transition from adhesion to deadhesion under mild conditions. It is suitable for non-traumatic transplantation and can Wear electronic devices.
Smart Images

Figure CN119307198A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogels, and in particular to a gel adhesive with strong adhesion and non-traumatic separation, and a preparation method and application thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Traditional adhesives mainly include bionic microstructure adhesives, pressure-sensitive adhesives, and chemical adhesives. These adhesives have strong adhesion on smooth surfaces, but poor adhesion on soft surfaces. They are likely to damage the object when peeled off, and are likely to be unable to be reused after peeling off. Reversible adhesive gel-type adhesives have good adhesion and reversible adhesion to soft surfaces, but the external stimuli required for de-adhesion of current reversible adhesive gel-type adhesives are relatively harsh, such as ultraviolet rays, magnetic fields, electric currents, or specific separation fluids, which further limits the application of reversible adhesive gel-type adhesives because these stimuli are harsh or even impossible to use on the skin.
[0004] In addition, existing reversible adhesive gel adhesives are difficult to simultaneously meet the requirements of strong adhesion and non-traumatic de-adhesion. For gel adhesives that only have strong adhesion, it is likely to cause skin pain, inflammation, or even damage when peeling; while for gel adhesives that can achieve non-traumatic separation, the adhesion is often poor. Therefore, the development of a gel-type adhesive with strong adhesion and the ability to achieve non-traumatic separation under mild conditions is an urgent problem to be solved. Summary of the invention
[0005] In view of this, the present invention provides a gel adhesive with strong adhesion and non-traumatic separation, and a preparation method and application thereof, which solves the problem that the gel adhesive in the prior art is difficult to simultaneously meet the requirements of strong adhesion and non-traumatic desorption. The gel adhesive prepared by the present invention also has excellent mechanical properties, good self-healing properties and ultra-high conductive properties, and has broad application prospects.
[0006] In a first aspect, the present invention provides a method for preparing a gel adhesive with strong adhesion and non-traumatic separation, comprising the following steps:
[0007] The fluorine-containing cationic surfactant, sodium citrate and trifluoroethyl acrylate are dissolved in water and stirred to form a uniform microemulsion; acrylic acid is added to the microemulsion and heated and stirred; then an initiator is added, stirred evenly and then heated and polymerized to obtain the microemulsion.
[0008] Preferably, the fluorine-containing cationic surfactant is [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide, and its structural formula is shown in formula (I):
[0009]
[0010] Preferably, the mass ratio of the fluorine-containing cationic surfactant, sodium citrate, trifluoroethyl acrylate, water and acrylic acid is (25-35):(3-7):(10-30):(80-100):(70-90).
[0011] Preferably, in the step of stirring to form a uniform microemulsion, the temperature is 20-30° C., the stirring time is 2-5 h, and the stirring speed is 300-500 rpm.
[0012] Preferably, in the step of adding acrylic acid to the microemulsion and heating and stirring, the heating temperature is 40 to 60° C., the stirring speed is 300 to 500 rpm, and the stirring time is 2 to 5 hours.
[0013] Preferably, the initiator is selected from any one of ammonium persulfate, potassium persulfate or sodium persulfate.
[0014] Preferably, the added amount of the initiator is 0.3-0.8 wt % of the mass of acrylic acid.
[0015] Preferably, the temperature of the heating polymerization is 55 to 70° C., and the time of the heating polymerization is 5 to 12 hours.
[0016] In a second aspect, the present invention provides a gel adhesive having strong adhesion and non-traumatic detachability prepared by the above preparation method.
[0017] In a third aspect, the present invention provides the use of the above-mentioned strongly adhesive and non-traumatically separable gel adhesive in non-traumatic transplantation, strain sensors or wearable electronic devices.
[0018] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0019] (1) The preparation method of the gel adhesive provided by the present invention is very simple and can be easily implemented in large-scale batch production.
[0020] (2) The gel adhesive prepared by the present invention has strong adhesion, and non-traumatic separation can be achieved by using a certain amount of water and / or ethanol, and the de-adhesion conditions are mild.
[0021] (3) The gel adhesive prepared by the present invention has low skin irritation, good mechanical properties, programmable adhesion properties and good conductivity, can achieve stable adhesion-deadhesion transition, and has potential applications in non-traumatic transplantation, strain sensors or wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 is a scanning electron micrograph of the interior of the P(AA-co-TFEA) gel adhesive of Example 3 of the present invention;
[0024] Figure 2 1 is a stress-strain diagram of Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention;
[0025] Figure 3 1 is a stress-strain diagram of Example 3, Example 4, Example 5 and Comparative Example 1 of the present invention;
[0026] Figure 4 is the adhesion strength curve of the P(AA-co-TFEA) gel adhesive obtained in Example 3 of the present invention to different substrates;
[0027] Figure 5 It is a comparison chart of the adhesion strength of the gel adhesive of Comparative Example 1 and Example 3 of the present invention under untreated, water-wetting treatment, and ethanol-wetting treatment;
[0028] Figure 6 is a graph showing the results of ten adhesion-deadhesion cycles of the P(AA-co-TFEA) gel adhesive of Example 3 of the present invention;
[0029] Figure 7 The P(AA-co-TFEA) gel adhesive obtained in Example 3 of the present invention monitors the relative resistance change of 50-400% strain;
[0030] Figure 8 These are the initial photographs of the P(AA-co-TFEA) gel adhesive obtained in Example 3 of the present invention attached to the skin (a), the photograph after adding an appropriate amount of water 24 hours later (b), and the photograph after peeling from the skin (c). DETAILED DESCRIPTION
[0031] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0032] The present invention provides a method for preparing a gel adhesive with strong adhesion and non-traumatic separation, comprising the following steps:
[0033] The fluorine-containing cationic surfactant, sodium citrate and trifluoroethyl acrylate are dissolved in water and stirred to form a uniform microemulsion; acrylic acid is added to the microemulsion and heated and stirred; then an initiator is added, stirred evenly and then heated and polymerized to obtain the microemulsion.
[0034] In the gel adhesive of the present invention, acrylic acid and trifluoroethyl acrylate are copolymerized to form a polymer chain, and the polyacrylic acid segment is used as a hydrophilic segment, and hydrogen bonds interact between the hydrophilic segments; the polytrifluoroethyl acrylate segment is used as a hydrophobic segment, and it can form a dynamic hydrophobic association with the fluorine-containing cationic surfactant, which serves as a physical crosslinking point, thereby giving the gel adhesive good mechanical strength and toughness. The fluorine-containing cationic surfactant can be adsorbed on the charged surface through electrostatic interaction, and can also be adsorbed on the hydrophobic surface through hydrophobic interaction. The gel adhesive of the present invention also exhibits huge cohesion and adhesion strength because it has a large number of reversible non-covalent interactions (hydrogen bonds, hydrophobic associations).
[0035] After a small amount of solvent (ethanol and / or water) is processed on the surface of the gel adhesive of the present invention (wetting), the hydrophobic aggregation part inside the gel is destroyed, and fluidity is improved, and polymer chains are more easily diffused to the surface of the substrate material, and the water molecules at the interface of the gel adhesive and the substrate material are repelled by the hydrophobic interface, and then adhere to the substrate material by various interactions (hydrogen bonds, electrostatic interactions, hydrophobic interactions, etc.), so the gel adhesive finally formed has strong adhesion. After a large amount of solvent (ethanol and / or water) is processed (infiltration), a large amount of polymer chain segments diffuse, causing viscosity to decrease, and it is easy to peel off. After the surface solvent (ethanol and / or water) volatilizes, the gel surface re-forms hydrophobic association, and it is achieved that adhesion is stable. Therefore, the gel adhesive provided by the present invention has strong adhesion, and non-traumatic separation and reversible adhesion can be realized under mild conditions.
[0036] In the present invention, the fluorine-containing cationic surfactant is [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide, and its structural formula is shown in formula (I): The introduction of the surfactant can form micelles on the one hand, so that the hydrophobic monomer trifluoroethyl acrylate is dispersed in water to form a microemulsion; on the other hand, it can form a dynamic hydrophobic association with the hydrophobic segments as a physical crosslinking point; in addition, it contains a quaternary ammonium salt cationic group, which is easy to form an electrostatic interaction with the negatively charged surface to improve the adhesion strength. In addition, it should be noted that although the fluorine-containing cationic surfactant contains a double bond, since the carbon-carbon double bond connects two trifluoromethyl groups, a perfluoroethyl group and a relatively large sterically hindered aminopropyl quaternary ammonium salt group, the CF bond has an extremely high bond energy, and the F atom has an extremely high shielding effect, which reduces the activity of the carbon-carbon double bond. Therefore, the fluorine-containing cationic surfactant does not participate in the polymerization reaction.
[0037] In the present invention, the mass ratio of the fluorine-containing cationic surfactant, sodium citrate, trifluoroethyl acrylate, water and acrylic acid is (25-35): (3-7): (10-30): (80-100): (70-90). The appropriate mass ratio can ensure that the prepared gel adhesive has good comprehensive performance.
[0038] In the present invention, in the step of stirring to form a uniform microemulsion, the temperature is 20 to 30°C, preferably room temperature; the stirring time is 2 to 5 hours, more preferably 2 to 3 hours, and the stirring speed is 300 to 500 rpm. Sufficient stirring can enable the fluorinated cationic surfactant to form stable micelles, ensuring sufficient fusion between the hydrophobic monomer and the surfactant.
[0039] In the step of adding acrylic acid to the microemulsion and heating and stirring, the heating temperature is 40-60° C., the stirring speed is 300-500 rpm, and the stirring time is 2-5 hours. The acrylic acid and the micelles are fully stirred to mix evenly, which is conducive to the polymerization reaction.
[0040] In the present invention, the initiator is selected from any one of ammonium persulfate, potassium persulfate or sodium persulfate. In one or more embodiments of the present invention, the initiator is preferably ammonium persulfate.
[0041] In the present invention, the added amount of the initiator is 0.3-0.8 wt % of the mass of acrylic acid. The initiator can decompose under heating conditions to generate free radicals, thereby initiating addition polymerization of double bonds.
[0042] In the present invention, the temperature of the heating polymerization is 55-70° C., and the heating polymerization time is 5-12 hours. Those skilled in the art can determine the appropriate polymerization temperature and time according to the type of the selected initiator.
[0043] The heating polymerization of the present invention is preferably carried out in a mold, that is, after adding the initiator and stirring evenly, the mixed solution is transferred to the mold for heating polymerization. In this embodiment, the stirring time after adding the initiator is controlled within 10 minutes to avoid polymerization reaction before transfer to the mold. The present invention does not impose any special restrictions on the size and material of the mold, and those skilled in the art can select and customize it according to actual needs.
[0044] The present invention also provides a gel adhesive with strong adhesion and non-traumatic separation obtained by the above preparation method. The gel adhesive of the present invention has strong adhesion, and can be non-traumatically separated by using a certain amount of water and / or ethanol, and the de-adhesion condition is mild; and it has low skin irritation, good mechanical properties, programmable adhesion properties and good conductivity, and can achieve stable transition from adhesion to de-adhesion.
[0045] The present invention also provides the use of the above-mentioned strongly adhesive and non-traumatically separable gel adhesive in non-traumatic transplantation, strain sensors or wearable electronic devices.
[0046] The technical solution of the present invention is further described below in conjunction with specific embodiments. Unless otherwise specified, the following embodiments have no special restrictions on the source of reagents, and commercially available products known to those skilled in the art can be used. The glass mold is homemade, and is composed of two glass plates of 10 cm×10 cm×2 cm and a silicone gasket.
[0047] In the following examples, AA represents acrylic acid, TFEA represents trifluoroethyl acrylate, P(AA-co-TFEA) represents a copolymer of acrylic acid and trifluoroethyl acrylate, APS represents ammonium persulfate, PE represents polyethylene, and PA represents polyamide.
[0048] In the following examples, the specific preparation method of the fluorinated cationic surfactant [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide is as follows:
[0049] ① Add 3-diethylaminopropylamine (30.97 g, 0.238 mol), Na2CO3 (20.90 g, 0.216 mol) and 80.0 mL of ether into a three-necked flask and stir evenly.
[0050] ② In an ice-water bath, add hexafluoropropylene dimer (D-2, 64.96 g, 0.216 mol) dropwise for 1 h. After the addition is complete, continue stirring for 0.5 h, remove the ice, naturally warm to room temperature, and reflux at 40 °C for 2 h.
[0051] ③ The product was dissolved and separated from the solid with ethanol, and the obtained solution was distilled under reduced pressure, and the solvent (ethanol, ether and unreacted hexafluoropropylene dimer and unreacted N,N-diethyl-1,3-propylenediamine) was removed by distillation under reduced pressure at 85°C to obtain the intermediate N,N-diethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropylenediamine.
[0052] ④ Take the synthesized N,N-diethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropylenediamine (4.10 g, 10.0 mmol), 40 mL of isopropanol, and 1-bromoethane (1.99 g, 12.0 mmol) in a single-necked flask, stir evenly, condense and reflux, and react at 65°C for 24 h.
[0053] ⑤ Rotary evaporate the reaction product at 65°C to remove the solvent and excess 1-bromoethane, and vacuum dry at 65°C for 24 hours to obtain the target product [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide.
[0054] Example 1
[0055] This embodiment provides a method for preparing a P(AA-co-TFEA) gel adhesive.
[0056] 3.0 g of [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide, 0.5 g of sodium citrate and 1.0 g of TFEA were dissolved in 9 mL of deionized water and stirred at 25 ° C for 3 h to obtain a microemulsion. Then 9.0 g of AA was added to the microemulsion and stirred at 50 ° C for another 1 h. Finally, the initiator APS (0.05 g) was added, stirred for 5 min, and the mixed solution was poured into a glass mold and heated at 60 ° C for 8 h to obtain a P(AA-co-TFEA) gel adhesive.
[0057] Example 2
[0058] This embodiment provides a method for preparing a P(AA-co-TFEA) gel adhesive.
[0059] 3.0 g of [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide, 0.5 g of sodium citrate and 2.0 g of TFEA were dissolved in 9 mL of deionized water and stirred at 25 ° C for 3 h to obtain a microemulsion. Then 9.0 g of AA was added to the microemulsion and stirred at 50 ° C for another 1 h. Finally, the initiator APS (0.05 g) was added, stirred for 5 min, and the mixed solution was poured into a glass mold and heated at 60 ° C for 8 h to obtain P (AA-co-TFEA) gel adhesive.
[0060] Example 3
[0061] This embodiment provides a method for preparing a P(AA-co-TFEA) gel adhesive.
[0062] 3.0 g of [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide, 0.5 g of sodium citrate and 3.0 g of TFEA were dissolved in 9 mL of deionized water and stirred at 25 ° C for 3 h to obtain a microemulsion. Then 9.0 g of AA was added to the microemulsion and stirred at 50 ° C for another 1 h. Finally, the initiator APS (0.05 g) was added, stirred for 5 min, and the mixed solution was poured into a glass mold and heated at 60 ° C for 8 h to obtain P (AA-co-TFEA) gel adhesive.
[0063] Figure 1 : is the internal scanning electron micrograph of the gel adhesive obtained in this example. It can be seen from the figure that the P(AA-co-TFEA) gel presents a dense porous structure, and the microstructure is mainly attributed to the highly cross-linked physical network. In addition, the dense porous structure increases the porosity of the gel, which may provide more conductive network paths to promote ion migration.
[0064] Example 4
[0065] This embodiment provides a method for preparing a P(AA-co-TFEA) gel adhesive.
[0066] 3.0 g of [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide, 0.5 g of sodium citrate and 2.0 g of TFEA were dissolved in 9 mL of deionized water and stirred at 25 ° C for 3 h to obtain a microemulsion. Then 8.0 g of AA was added to the microemulsion and stirred at 50 ° C for another 1 h. Finally, the initiator APS (0.05 g) was added, stirred for 5 min, and the mixed solution was poured into a glass mold and heated at 60 ° C for 8 h to obtain a P(AA-co-TFEA) gel adhesive.
[0067] Example 5
[0068] This embodiment provides a method for preparing a P(AA-co-TFEA) gel adhesive.
[0069] 3.0 g of [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide, 0.5 g of sodium citrate and 1.0 g of TFEA were dissolved in 9 mL of deionized water and stirred at 25 ° C for 3 h to obtain a microemulsion. Then 7.0 g of AA was added to the microemulsion and stirred at 50 ° C for another 1 h. Finally, the initiator APS (0.05 g) was added, stirred for 5 min, and the mixed solution was poured into a glass mold and heated at 60 ° C for 8 h to obtain P (AA-co-TFEA) gel adhesive.
[0070] Comparative Example 1
[0071] Compared with Example 1, this comparative example differs in that [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide and TFEA are not added. The specific preparation method is as follows:
[0072] Sodium citrate was dissolved in 9 mL of deionized water and stirred at 25°C for 3 h to obtain a sodium citrate solution. Then 9.0 g of AA was added to the sodium citrate solution and stirred at 50°C for another 1 h. Finally, initiator APS (0.05 g) was added and stirred for 5 min. The mixed solution was poured into a glass mold and heated at 60°C for 8 h to obtain the product.
[0073] Test example
[0074] 1. Stress-strain curve determination:
[0075] Figure 2 1 is a stress-strain diagram of Example 1, Example 2, Example 3 and Comparative Example 1. As can be seen from the figure, as the content of the hydrophobic monomer TFEA increases, the gel fracture strength increases and the elongation at break increases. This is because the increase in the amount of hydrophobic monomer increases the micelle concentration, and more physical cross-linking sites are formed inside the gel, which improves the mechanical properties of the gel.
[0076] Figure 3 1 is a stress-strain diagram of Example 3, Example 4, Example 5 and Comparative Example 1. As can be seen from the figure, as the content of acrylic acid monomer increases, the gel fracture strength increases and the elongation at break increases. This is because there is an interaction force between acrylic acid monomers. When the content of acrylic acid increases, the hydrogen bond interaction of the internal network structure of the gel increases, so that the mechanical properties of the gel are improved.
[0077] 2. Adhesion test:
[0078] Figure 4The following is a comparison chart of the adhesion strength of the P(AA-co-TFEA) gel adhesive obtained in Example 3 to different substrates after ethanol wetting treatment, including glass, pigskin, iron (Fe), aluminum (Al), polyethylene (PE) and polyamide (PA). It can be seen that the gel adhesive after ethanol wetting treatment has strong adhesion to different materials, but the gel has different adhesion strengths to different substrates, which is because the gel has different interactions with different substrates.
[0079] Figure 5 This is a comparison of the adhesion strength of the gel adhesives of Example 1 and Example 3 to the glass sheet under untreated, water wetting treatment, and ethanol wetting treatment. It can be seen that the adhesion strength of the gel adhesive of Example 3 of the present invention is significantly improved after being wetting with water and ethanol, while the adhesion strength of the gel adhesive in Example 1 does not change significantly after being wetting with water and ethanol, indicating that the gel adhesive of Example 3 has excellent adhesion responsiveness and can achieve high-strength adhesion.
[0080] 3. Adhesion-deadhesion experiment:
[0081] The adhesion strength of the P(AA-co-TFEA) gel adhesive of Example 3 was measured by lap shear. Before making the sample, the substrate material (glass) was cleaned with deionized water and ethanol and dried completely. The surface of the gel was moistened with ethanol and then attached to the surface of the substrate material, and then overlapped with another substrate material, with a contact area of 2.5×2.5 cm 2 , pre-press for three minutes, pull the sample at a fixed speed of 30mm / min on the Spectra universal tensile machine until it separates. Then rinse and peel off the glass sheet attached to the gel adhesive with water, and quickly dry the gel adhesive sample in a 60℃ blast oven to evaporate the water on the sample surface, and the adhesion on the sample surface will decrease rapidly. Then, perform the lap shear test on the sample again in the same way, that is, complete an adhesion-de-adhesion test, repeat ten cycles, and the test results are as follows: Figure 6 shown.
[0082] from Figure 6 It can be seen that in ten cycles of adhesion experiments, the adhesion strength of P(AA-co-TFEA) gel adhesive to glass remained stable and could be completely peeled off, indicating that it has the ability to be reused.
[0083] 4. Strain sensing performance measurement:
[0084] Figure 7The P(AA-co-TFEA) gel adhesive obtained in Example 3 of the present invention monitors the relative resistance change of 50-400% strain. It can be seen that the relative resistance increases with the increase of gel strain. At the same time, the P(AA-co-TFEA) gel adhesive can sensitively monitor a tiny strain of 50%, so it can be used for human body sensing.
[0085] 5. Skin irritation test:
[0086] Figure 8 The initial photo (a) of the P(AA-co-TFEA) gel adhesive obtained in Example 3 of the present invention attached to the skin, the photo (b) after adding a proper amount of water 24 hours later, and the photo (c) after peeling from the skin. After being moistened with a small amount of water, the gel adhesive can be well attached to the skin surface, and then after 24 hours, a proper amount of water is added through a dropper, and it can be easily peeled off without residue on the skin, and it will not cause skin allergies and redness, proving that it can be in contact with the skin for a long time and used in wearable human sensing devices.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a gel adhesive with strong adhesion and non-traumatic separation, characterized in that: The steps include: The fluorine-containing cationic surfactant, sodium citrate and trifluoroethyl acrylate are dissolved in water and stirred to form a uniform microemulsion; acrylic acid is added to the microemulsion and heated and stirred; then an initiator is added, stirred evenly and then heated and polymerized to obtain the microemulsion.
2. The preparation method according to claim 1, characterized in that The fluorine-containing cationic surfactant is [N,N-diethyl-N-ethyl-N'-(2-trifluoromethyl-1-pentafluoroethyl)perfluoropropyleneaminopropyl]ammonium bromide, and its structural formula is shown in formula (I):
3. The preparation method according to claim 1, characterized in that: The mass ratio of the fluorine-containing cationic surfactant, sodium citrate, trifluoroethyl acrylate, water and acrylic acid is (25-35): (3-7): (10-30): (80-100): (70-90).
4. The preparation method according to claim 1, characterized in that: In the step of stirring to form a uniform microemulsion, the temperature is 20-30° C., the stirring time is 2-5 hours, and the stirring speed is 300-500 rpm.
5. The preparation method according to claim 1, characterized in that: In the step of adding acrylic acid to the microemulsion and heating and stirring, the heating temperature is 40-60° C., the stirring speed is 300-500 rpm, and the stirring time is 2-5 hours.
6. The preparation method according to claim 1, characterized in that: The initiator is selected from any one of ammonium persulfate, potassium persulfate or sodium persulfate.
7. The preparation method according to claim 1, characterized in that: The added amount of the initiator is 0.3-0.8 wt % of the mass of acrylic acid.
8. The preparation method according to claim 1, characterized in that: The temperature of the heating polymerization is 55-70° C., and the time of the heating polymerization is 5-12 hours.
9. A gel adhesive having strong adhesion and non-traumatic separation obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the strongly adhesive and non-invasively separable gel adhesive as claimed in claim 9 in non-invasive transplantation, strain sensors or wearable electronic devices.